2015
DOI: 10.1681/asn.2014090906
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Stabilization Ameliorates Autoimmune Anti-Myeloperoxidase Glomerulonephritis

Abstract: Observations in experimental murine myeloperoxidase (MPO)-ANCA-associated vasculitis (AAV) show mast cells degranulate, thus enhancing injury as well as producing immunomodulatory IL-10. Here we report that, compared with biopsy specimens from control patients, renal biopsy specimens from 44 patients with acute AAV had more mast cells in the interstitium, which correlated with the severity of tubulointerstitial injury. Furthermore, most of the mast cells were degranulated and spindle-shaped in patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…In agreement with an important role of MC degranulation in the acceleration of rejection our data show that pharmacological blockade of degranulation with cromolyn had a major effect on the kinetics of graft rejection approaching the half-lives achieved with the absence of MCs alone. Although the action of cromolyn on MC degranulation in mice was challenged ( 62 ) many other studies reported significant effects with this compound ( 63 65 ). It is possible that the time of administration to engender active metabolites may play an important role in different species.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with an important role of MC degranulation in the acceleration of rejection our data show that pharmacological blockade of degranulation with cromolyn had a major effect on the kinetics of graft rejection approaching the half-lives achieved with the absence of MCs alone. Although the action of cromolyn on MC degranulation in mice was challenged ( 62 ) many other studies reported significant effects with this compound ( 63 65 ). It is possible that the time of administration to engender active metabolites may play an important role in different species.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells contribute to peripheral tolerance to MPO, through IL-10 mediated effects on regulatory T cells (Figure 1B) (93). Furthermore, autoimmunity and GN can be attenuated by disodium cromoglicate, a mast cell stabilizer (94).…”
Section: Active Anti-mpo Glomerulonephritis In Micementioning
confidence: 99%
“…In kidney bioptic specimens from patients with autoimmune anti‐MPO glomerulonephritis, a higher number of interstitial degranulated mast cells was recognizable as compared with controls . Administration of disodium cromoglycate, a mast cell‐stabilizing agent, inhibited the development of experimental glomerulonephritis and mast cell presence within the kidney . A higher number adventitial mast cells was recognizable in the dissected portion of coronary arteries in the course of eosinophilic coronary periarteritis …”
Section: Clinical Evidence Of the Involvement Of Mast Cells In Vasculmentioning
confidence: 99%